2009
DOI: 10.1002/cne.22079
|View full text |Cite
|
Sign up to set email alerts
|

Increase of intracellular Ca2+ by P2Y but not P2X receptors in cultured cortical multipolar neurons of the rat

Abstract: The expression and functionality of P2X/P2Y receptor subtypes in multipolar nonpyramidal neurons of mixed cortical cell cultures were investigated by means of immunocytochemistry and fura-2 microfluorimetry. The morphological studies revealed that most of the neurons are immunoreactive for GABA and express a range of P2X/P2Y receptors, predominantly of the P2X(2,4,6) and P2Y(1,2) subtypes. P2X(1) and P2X(7) receptor immunoreactivity (IR) was found on thin axon-like processes and presynaptic structures, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
4
1
1
Order By: Relevance
“…β‐NAD + failed to elicit Ca 2+ transients in the absence of extracellular Ca 2+ , implying that the rapid neuronal responses are due to influx of Ca 2+ from the extracellular space. These results differ from a recent report in rat cultured neurons (Fischer et al. , 2009), which has demonstrated more modest Ca 2+ increases following much longer exposures (10 s) to lower P2 receptor agonist concentrations (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…β‐NAD + failed to elicit Ca 2+ transients in the absence of extracellular Ca 2+ , implying that the rapid neuronal responses are due to influx of Ca 2+ from the extracellular space. These results differ from a recent report in rat cultured neurons (Fischer et al. , 2009), which has demonstrated more modest Ca 2+ increases following much longer exposures (10 s) to lower P2 receptor agonist concentrations (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Previously, the linkage between P2X7 receptor and Panx1 was also considered to be necessary for P2X7-mediated generation of ROS and proinflammatory cytokines in macrophages [ 89 , 90 ]. On the other hand, neurons also express both P2X7 and Panx1, but their functionality remains controversial [ 91 93 ]. Our current studies have shown that inhibition of Panx1 dampens extracellular ATP levels; however, it does not inhibit P2X7 receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we tested whether the beneficial effects of blocking P2X7Rs in Mecp2 308/Y mice can be achieved by primarily inhibiting P2X7Rs in peripheral tissues (e.g., blood, brain's perivascular spaces and meninges). Brilliant Blue G (BBG) is a U.S. Food and Drug Administration-approved drug and has been shown to block P2X7R-mediated increase in membrane permeability and macroscopic currents in cell cultures and spinal cord slices 21,46 . Previous studies have shown that BBG has low penetrance to the CNS parenchyma (brain to plasma ratiõ 0.01).…”
Section: Pharmacological Block Of P2x7rs Improves Social Behaviormentioning
confidence: 99%